(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Computer memory is expensive and the recording of data captured by a webcam needs memory. In order to minimize the memory usage in recording data from human motion as recorded from the webcam, this algorithm will use motion detection as applied to a process to measure the change in speed or vector of an object in the field of view. This application only works if there is a motion detected and it will automatically save the captured image in its designated folder.